Exploring the Causal Structures of Almost Commutative Geometries - Franco, N.; Eckstein, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
We investigate the causal relations in the space of states of almost commutative Lorentzian geometries. We fully describe the causal structure of a simple model based on the algebra S(R¹,¹)⊗M₂(C), which has a non-trivial space of internal degrees of freedom. It turns out that the causality condition imposes restrictions on the motion in the internal space. Moreover, we show that the requirement of causality favours a unitary evolution in the internal space.